2016
DOI: 10.5014/ajot.2016.018069
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Interventions in Physical Rehabilitation: A Scoping Review

Abstract: A scoping review was conducted to describe how mindfulness is used in physical rehabilitation, identify implications for occupational therapy practice, and guide future research on clinical mindfulness interventions. A systematic search of four literature databases produced 1,524 original abstracts, of which 16 articles were included. Although only 3 Level I or II studies were identified, the literature included suggests that mindfulness interventions are helpful for patients with musculoskeletal and chronic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
(17 reference statements)
2
26
0
2
Order By: Relevance
“…Most forms of informal mindfulness, generally described as an additional activity in which one applies a mindful attention, such as in yoga, have yielded measurable benefits in stress reduction, mental health, and other health conditions, including reduced pain perception (Carsley & Heath, 2018;Hardison & Roll, 2016;Strauss et al, 2014). Informal mindfulness is defined by the application of mindful awareness while experiencing participation in everyday activities without perseveration on competing thoughts, feelings, and body sensations (Kabat-Zinn, 2003).…”
Section: History Of Mindfulness In Occupational Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Most forms of informal mindfulness, generally described as an additional activity in which one applies a mindful attention, such as in yoga, have yielded measurable benefits in stress reduction, mental health, and other health conditions, including reduced pain perception (Carsley & Heath, 2018;Hardison & Roll, 2016;Strauss et al, 2014). Informal mindfulness is defined by the application of mindful awareness while experiencing participation in everyday activities without perseveration on competing thoughts, feelings, and body sensations (Kabat-Zinn, 2003).…”
Section: History Of Mindfulness In Occupational Therapymentioning
confidence: 99%
“…Secondary review articles revealed helpful information from seven additional articles and four texts. First, in a scoping review of mindfulness techniques applied in physical rehabilitation via breath, yoga, meditation, and other non-specified activities (Hardison & Roll, 2016), the authors found support for the use of these stand-alone mindfulness trainings to enhance client self-efficacy and disease management, improve adaptation to disability and quality of life perception, and reduce pain and depression associated with neurocognitive and neuromotor disorders. Of the 14 articles reviewed, however, only two instances were identified in which occupational therapy facilitated the intervention.…”
Section: Summary Of the Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggest that mindfulness training can be a rather robust intervention to improve mental health outcome and especially stress, even when mindfulness is administrated and delivered in a shorter format, online on internet (Spijkerman, Pots, & Bohlmeijer, 2016). Short term mindfulness intervention could be of benefit, but so far shorter mindfulness interventions in rehabilitation are not yet well established (Hardison & Roll, 2016), especially when considering life-long mental health issues. We also wanted to enable for participants to share their experiences, over time and learn from each other by the specific way that inquiry is held during the class by the mindfulness teacher.…”
Section: The Train 4 Good Programmentioning
confidence: 99%
“…Occupational therapists are holistic, client‐centered health practitioners who play an integral role in PD management, aiming to work alongside clients to enhance independence, physical functioning, participation in meaningful activities, and overall quality of life (Martin & Wieler, ). In addressing the psychological needs of their clients, numerous evidence‐based psychosocial strategies are considered to be within the scope of occupational therapy practice, including goal setting, mindfulness, CBT, relaxation, MI and positive reinforcement, psychoeducation, and social support (American Occupational Therapy Association, ; Hardison & Roll, ; Nielsen, Stube, & Bass, ).…”
Section: Introductionmentioning
confidence: 99%